INFLORESCENCE WITH TRICOLPATE POLLEN GRAINS FROM THE CENOMANIAN OF TSCHULYMO-YENISEY BASIN, WEST SIBERIA - Krassilov V.A.; Golovneva L.B. (My University, 2001)
A new taxon Freyantha sibirica gen. et sp. nov. is erected for a delicate racemose inflorescence from the Cenomanian of the Tchulymo-Yenisey Basin, West Siberia. The inflorescence bears male flowers of partly connate stamens that produced tricolpate reticulate pollen grains. The flowers are subtended by calyptrate bracts. The taxonomically significant features of the general inflorescence morphology, prophylls, floral bracts, stamens and pollen grains are shared with different angiosperm groups, such as the Menispermaceae and Sargentodoxaceae. Prominent glands on the floral bracts indicate pollination by nectar-sucking insects.
Keywords: Cenomanian; Tchulymo-Yenisey Basin; West Siberia; Freyantha sibirica; Мезозой::Меловая::Верхний::Сеноманский; Mesozoic::Cretaceous::Upper::Cenomanian